Efficacy of Heart Rate Variability Biofeedback for Somatic Symptom Disorder: A Pilot Randomized Controlled Trial. Issue 1 (3rd January 2023) - Krempel, Laura; Martin, Alexandra
ABSTRACT: Objective: Patients with somatic symptom disorder (SSD) often receive targeted intervention only after a long duration of illness. Moreover, the reported effect sizes of interventions for SSD are small. Therefore, improvement and evaluation of interventions are needed. Preliminary evidence suggests autonomic imbalance, for example, lower heart rate variability (HRV) in SSD. HRV biofeedback (HRV-BF) as a method for self-regulation shows initial positive effects in chronic pain and functional syndromes. The aim of this study was to evaluate the efficacy of a brief HRV-BF intervention for SSD. Methods: Of a total of 50 participants with SSD ( Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ) who were recruited and randomly assigned to four sessions of HRV-BF ( n = 25) or autogenic training (AT; n = 25), 49 participants were analyzed (female, 77.6%; mean [standard deviation] age = 45.3 [14.4] years). The primary outcomes were somatic symptom severity (Screening for Somatoform Disorders, numeric rating scale) and HRV. Secondary outcomes were psychological characteristics of SSD (e.g., the Somatic Symptom Disorder 12 scale, health concerns, emotion regulation). The data were collected before and after intervention and were analyzed with repeated-measures analyses of variance and post hoc t tests. Results: Symptom severity improved after both, HRV-BF and AT. Standard Deviation of the NN Interval and psychological symptoms improved significantly more strongly in the HRV-BF than in the AT group (e.g., Standard Deviation of the NN Interval: η p 2 interaction = 0.10, p = .047). Conclusions: The improvements in somatic symptoms, but specifically in cognitive-affective symptoms and autonomic regulation, suggest that HRV-BF with only four sessions is a potentially useful intervention option for SSD. Thus, adding this short HRV-BF intervention to existing psychological treatments for SSD may be promising. Trial Registration : German Clinical Trial Register identifier DRKS00017099 (https://www.drks.de ).